How do you measure a carbon footprint? - Boratyński, Jakub; Świeczewska, Iwona D. (W poszukiwaniu zielonego ładu, 2022)
This chapter deals with calculating the carbon footprint. The methodological part is devoted to the presentation of the use of input-output tables from the WIOD (World Input-Output Database) and data on greenhouse gas emissions developed by the JRC (Joint Research Center of the European Commission). The practical part concerns the total CO2 emissions in the chain of final production of cars in Germany.